Development of Professional Competence of Students of Energy Studies Based on Case Technologies (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In modern society, the training of highly qualified specialists in the energy sector is one of the most pressing issues. Technological changes and global challenges in the energy field require students to possess practical skills alongside theoretical knowledge. From this perspective, the application of innovative pedagogical techniques, particularly case study methods, in the educational process is of paramount importance. This article analyzes the potential for developing the professional competence of energy engineering students through the use of case study technologies.